2003
DOI: 10.3408/jasti.8.59
|View full text |Cite
|
Sign up to set email alerts
|

The Quantitative Classification of Hair Form and Its Application to the Forensic Comparison of Japanese Head Hair

Abstract: A method for expressing the hair form of Japanese head hair in the form of numerical data was investigated with regard to inter-individual comparisons, and the utility of the method was evaluated based on the screening of experimental evidential hair samples by cluster analysis.The four characteristics used for the quantiˆcation of hair form included a basic characteristic (5 categories), an additional characteristic (4 categories) and 2 peculiar morphologies (3 categories). The hair forms of Japanese head hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In damaged hairs, considerable skill is required to discriminate between dog and cat hairs by morphological examination. We recently reported that numerical data obtained from hair morphologies could be used in a statistical interpretation of the morphological features of human hairs [16,25].…”
Section: Introductionmentioning
confidence: 99%
“…In damaged hairs, considerable skill is required to discriminate between dog and cat hairs by morphological examination. We recently reported that numerical data obtained from hair morphologies could be used in a statistical interpretation of the morphological features of human hairs [16,25].…”
Section: Introductionmentioning
confidence: 99%